THE IMPACT OF HYPERTENSION, HYPERCHOLESTEROLEMIA, AND SMOKING HISTORY ON STROKE INCIDENCE AT DR. R. SOEDJONO SELONG REGIONAL HOSPITAL - Ningsih, Dera Ayu; Faridi, M. Sofyan; Putra, Risky Irawan; Utami, Sukandriani (UNG, 2026)
Stroke is a major cause of morbidity and mortality and remains a public health problem, including in East Lombok Regency. The high incidence of stroke is closely related to modifiable risk factors, such as hypertension, hypercholesterolemia, and smoking habits. The novelty of this study lies in the analysis of stroke risk factors based on patient data from Dr R. Soedjono Selong Regional General Hospital, the main referral hospital in East Lombok, which has been reported only to a limited extent. This study aims to analyse the relationship between hypertension, hypercholesterolemia, and smoking history with stroke incidence at Dr R. Soedjono Selong Regional General Hospital. This study is an observational, analytical, cross-sectional study conducted in October–November 2025 on 84 respondents selected using a purposive sampling technique. Data obtained from medical records and structured interviews were then analysed using the chi-square test. The results showed that stroke incidence was found in 57.1% of respondents. Hypertension and hypercholesterolemia were shown to have a significant relationship with stroke incidence, with p-values of 0.005 and 0.000, respectively (p 0.05), while smoking history did not show a significant relationship with stroke incidence (p-value = 0.243). The conclusion of this study shows that hypertension and hypercholesterolemia are the main risk factors associated with stroke incidence, so that control of these two factors needs to be a priority in stroke prevention efforts at the health service level.